CO-FUNCTIONING OF LECTINS OF MULTICOMPONENT PROBIOTIC AND POTENTIAL PROBIOTIC COMPARTMENT OF BIOTOPE ON THE EXAMPLE OF AUTOREGULATOR LACTOBACILLUS SYSTEM - M. V. Lakhtin (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
Using lectins of Acilact, clinical isolates of Lactobacillus from vaginal biotope were screened. Lactobacilli of the biotopes were classified to functional groups. Results indicate autoregulation signal properties of probiotic microbial lectins.